POLITENESS STRATEGIES USED BY THE MAIN CHARACTER OF SHERLOCK HOLMES A GAME OF SHADOW MOVIE - PARASAYU, MELISA DYAH (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Face Threatening Act (FTA), Politeness StrategiesThis study is about FTA and politeness strategies performed by Holmes as the main character in Sherlock Holmes, “A Game of Shadow” movie. The objectives are to find out the types of face threatening act and politeness strategies performed by Holmes when he is having conversation with his interlocutors.This study was classified as a qualitative research and categorized into document analysis because it analyzed the script and conversations performed by Holmes on Sherlock Holmes, “A Game of Shadow” movie.From the result of analysis, the main character of movie entitled Sherlock Holmes, ‘A Game of Shadow’ named Sherlock Holmes performed face threatening acts (FTAs) in his utterances based on the theory of Brown and Levinson (1987). The writer found 111 utterances of Sherlock Holmes containing Face-Threatening Acts. By paying attention to the face being threatened, negative face ranked the first for 86 times and positive face ranked the second for 25 times. In performing FTA, the speaker intended to use strategies to mitigate the damage to the hearers. Holmes intended to maintain good relationship with others and did not want to impinge the hearers. Based on the data, the kinds of FTA strategies performed by Holmes are 44 negative politeness, 40 positive politeness, 18 bald on-record, and 14 off-record. Therefore, Holmes mostly performed negative politeness strategy in his conversation.Further study about politeness can be carried out to find out the factor influencing the choice of each strategy of politeness. Because politeness is very important in interaction, the writer hopes that the readers can learn more about it and explore it in the diverse culture of Indonesian ethnic group.